2009
DOI: 10.1089/dia.2009.0002
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Compartments: Interstitial Versus Blood Glucose Monitoring

Abstract: Self-monitoring of blood glucose was described as one of the most important advancements in diabetes management since the invention of insulin in 1920. Recent advances in glucose sensor technology for measuring interstitial glucose concentrations have challenged the dominance of glucose meters in diabetes management, while raising questions about the relationships between interstitial and blood glucose levels. This article will review the differences between interstitial and blood glucose and some of the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
257
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(268 citation statements)
references
References 59 publications
4
257
2
5
Order By: Relevance
“…The lag (5-10 min) is greatest during times of rapidly changing plasma glucose levels and can affect calibrations and long-term accuracy of the CGM. 53 Another potential problem is the physiologic change in the interstitial fluid that accompanies pregnancy and may impact sensor accuracy, although one study found that this was not relevant for the sensor used. 44 As with any medical device, CGMs can be costprohibitive.…”
Section: Caveats About Cgm Use In Pregnancymentioning
confidence: 99%
“…The lag (5-10 min) is greatest during times of rapidly changing plasma glucose levels and can affect calibrations and long-term accuracy of the CGM. 53 Another potential problem is the physiologic change in the interstitial fluid that accompanies pregnancy and may impact sensor accuracy, although one study found that this was not relevant for the sensor used. 44 As with any medical device, CGMs can be costprohibitive.…”
Section: Caveats About Cgm Use In Pregnancymentioning
confidence: 99%
“…While intraarterial (IA) and intravenous (IV) measurements are not practically usable in outpatients, subcutaneous (SC) sensing has become the standard for continuous glucose monitoring (CGM) during the last 15 years. However, state of the art SC glucose sensing technologies with enzyme-based amperometric technology still face challenges with time delays and slow dynamics (Basu et al, 2013;Cengiz and Tamborlane, 2009;Boyne et al, 2003;Davey et al, 2010) as well as poor robustness (Helton et al, 2011;Mensh et al, 2013), even though recent publications indicate that novel CGM systems may be less prone to such problems (Garcia et al, 2013;Bailey et al, 2015). These challenges originate partly from the sensor technology and partly from the physiologically slow glucose transfer between intravascular glucose levels and glucose levels in subcutaneous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…While beneficial for profiling overall glycaemic management, considerable CGM error was noted when glucose levels were changing rapidly ( Fig. 3), as has previously been documented [30][31][32].…”
Section: Glycaemic Responses and Change In Glucagon Levelsmentioning
confidence: 65%